Comparative Effects of Spray-Dried Plasma and Bacitracin Methylene Disalicylate on Intestinal Development in Broiler Chicks - Jababu, Y.; Blue, C.; Ferket, P.R.; Fasina , Y.O. (International Journal of Poultry Science, 2020)
Background and Objectives: Spray-dried plasma (SDP) is a bioactive feed additive that frequently improves broiler growth performance and may therefore replace antibiotic growth promoters (AGPs). To improve our understanding of SDP mechanisms of action, a 2-week experiment was conducted to compare the potency of porcine SDP and bacitracin methylene disalicylate (BMD) antibiotic to stimulate intestinal development in neonate chicks. Materials and Methods: Day-old (288) Ross 708 broiler male chicks were obtained from a commercial hatchery and randomly assigned to 6 treatments in a completely randomized design. Treatments consisted of chicks given unmedicated corn-soybean meal basal diet containing no BMD or SDP (CX), at 0.055 g kg–1 diet (MX), SDP at 10 g kg–1 diet (SP1), SDP at 20 g kg–1 diet (SP2), SDP at 30 g kg–1 diet (SP3) and SDP at 40 g kg–1 diet (SP4). On day 3, 7 and 14 of experiment, intestinal maltase activity was determined. Villi morphometrics was also measured in the jejunum (d 7). Results: On day 7, all chicks that consumed SDP and BMD had lower villus: crypt ratio (p = 0.0006) and higher goblet cell density (p < 0.0001) compared to CX. Furthermore, on day 14, ileal maltase activity was higher for all chicks that consumed SDP (3.036-3.065 μg glucose/min/mL/μg protein, p < 0.0001) compared to CX (3.025 μg glucose/min/mL/μg protein). Conclusion: Like BMD antibiotic, dietary SDP at 30 or 40 g kg–1 diet improves feed conversion ratio in chicks in-part, by increasing ileal maltase activity, reducing intestinal villus/crypt ratio (indicative of ongoing villi renewal/regeneration) and increasing goblet cell density.